Peer reviewers: Providing credibility. Issue 6 (30th November 2015) - Unknown
Abstract : Celebrate your profession just in time for Perioperative Nurses Week, by becoming a peer reviewer. You will provide credibility to the journal, enhance your perioperative nursing practice, and improve patient care.